2020
DOI: 10.3233/apc200159
|View full text |Cite
|
Sign up to set email alerts
|

Device Authentication and Secure Routing in MANET for Internet of Things

Abstract: In the next generation of communication mobile adhoc network (MANET) will play a major role in Internet of Things (IoT).MANET can be defined as a network among a group of nodes with no infrastructure. Internet of Things is the composition of a variety of networks like Wi-Fi, ZigBee, Wireless Sensor Networks (WSNs). MANETs, and Radio Frequency Identifier (RFID). There is a need for the compatibility of MANET with IoT for the deployment of smart infrastructure. Authenticity and security in communication between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In addition to the 5DNB system discussed in the previous section, we consider five additional crystal systems comprising A-DNA (137D 48 ), Z-DNA(1LJX 49 ), and three other B-DNAs (1D23, 50 119D 51 and 1BNA 52 ) as summarized in Table 1. These systems were chosen for study based on their resolution, size, structural diversity, and near roomtemperature data collection.…”
Section: Benchmark Dna Crystal Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the 5DNB system discussed in the previous section, we consider five additional crystal systems comprising A-DNA (137D 48 ), Z-DNA(1LJX 49 ), and three other B-DNAs (1D23, 50 119D 51 and 1BNA 52 ) as summarized in Table 1. These systems were chosen for study based on their resolution, size, structural diversity, and near roomtemperature data collection.…”
Section: Benchmark Dna Crystal Systemsmentioning
confidence: 99%
“…All studied systems except for the A-DNA (137D 48 ) have some form of coaxial stacking of the helices, which is common in nucleic acid crystals. Z-DNA (1LJX 49 ) and the two decamer B-DNAs (5DNB 43 and 1D23 50 ) form uniform columns and behave like "infinite" DNA helices, where the only coaxial interaction between molecules is base stacking. The dodecamer B-DNA (119D 51 and 1BNA 52 ) have zig-zag coaxial stacking induced by the special inter-molecular interactions denoted as Dickerson Interactions (DI) 55 where sets of three base pairs at both ends hydrogen bond with the consecutive molecules.…”
Section: Torsional Angle Distributionsmentioning
confidence: 99%
“…Previous studies showed that Gli2 overexpression accelerates cell cycle progression and augments proliferation in tumor cells, whereas Gli2 inhibition blocks tumor growth in vitro and even in vivo when Gli2 is molecularly repressed using genetic techniques in bone metastatic cancer cell lines. 60,61 This motivated the hypothesis that blocking Gli activity in metastatic breast tumors could obstruct their potential to establish in bone and adopt a bone-destructive phenotype. However, histomorphometric analysis of the tibiae from treated mice showed no significant decrease in overall tumor burden in 10% Aln-GANT58-treated mice (Figure S12A).…”
Section: Gant58-btnp Treatment Reduces Bone Destruction In a Mouse Intracardiac Model Of Bone Metastasismentioning
confidence: 99%